Carbon partitioning and microstructure evolution during tempering of an Fe-Ni-C steel. (November 2019) - Harding, I.; Mouton, I.; Gault, B.; Raabe, D.; Kumar, K.S.
Abstract: Partitioning of C during tempering of quenched Fe-9.6Ni-0.5C-0.6Mn-0.6Mo-0.7Cr-0.1V (at.%) steel is determined by atom probe tomography and the resulting microstructure is described. The precipitated austenite size, together with its C and Ni content control its thermal stability and these can vary differently with tempering time and temperature. Thus, both austenite and strong carbide formers compete for the available C early in the process. Due to widely different transport kinetics, C likely plays a dominant role early but is either fully consumed or its role diminishes by dilution, and Ni partitioning eventually takes over as the austenite stability-controlling species. Graphical abstract: Unlabelled Image